Analysis of Soil Improvement using Stone Columns in Reducing Liquefaction Potential (Case study: Runway 3 of Soekarno-Hatta Airport) - Mina, Enden; Kusuma, Rama Indera; Fathonah, Woelandari; Tarihoran, Rona Ulita (JURUSAN TEKNIK SIPIL, 2023)
This research discusses the use of stone columns in increasing the value of the safety factor on soils that have the potential to experience liquefaction. This study aims to determine the safety factor value of sandy soil in the study area and the safety factor value after Stone Column planning. The method used to determine the value of liquefaction potential is the method of Seed et al, based on the interpretation of SPT (Standard Penetration Test) data and using the stone column as a soil improvement method. Based on the results of the study, it is known that each point has the potential to experience liquefaction except at points BH 7, BH 8, and BH 9. The LPI value is > 15, so the research area has the potential to experience liquefaction. Before planning the safety factor value is 0.43-0.87 and after planning the stone column using an equilateral triangle pattern the safety factor value increases to 1.21-2.3 while using a square pattern of 0.95-1.94.